PRECISION OF MATHEMATICAL VERBS IN GRADE 12 LEBANESE NATIONAL EXAMS - Shehayeb, Sanaa (International Journal of Research -GRANTHAALAYAH, 2023)
This study aims at analyzing a recent copy of the Lebanese mathematics national exams in terms of precision of action verbs as well as classification of free-response items according to Porter’s rubric related to language associated with performance outcomes and two-dimensional Bloom Revised Taxonomy. Results showed that the verbs were classified at different levels. The levels were all tackled in the exam which shows variety of questions except for the highest Porter level. The higher thinking level questions as specified by Porter and Bloom constituted around 30% of the exam. Similar studies targeting all national mathematics exams are recommended.